1987
DOI: 10.1128/iai.55.1.193-197.1987
|View full text |Cite
|
Sign up to set email alerts
|

Presence and expression of aerobactin genes in virulent avian strains of Escherichia coli

Abstract: Virulent and nonvirulent isolates of avian Escherichia coli were tested for the presence of aerobactin genes by colony hybridization with a specific gene probe constructed from plasmid pABN1 (A. Bindereif and J. B. Neilands, J. Bacteriol. 153:1111Bacteriol. 153: -1113Bacteriol. 153: , 1983. Positive hybridization with the gene probe was highly correlated with virulence, as measured by the 50% lethal dose of the strains for chicks. Evidence for the expression of aerobactin genes in the virulent strains was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
24
1
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 33 publications
3
24
1
1
Order By: Relevance
“…The presence of aerobactin biosynthetic genes in avian septicemic E. coli is in agreement with previous reports which found that most of these strains carry a plasmidencoded aerobactin iron uptake system [7]. However the lack of both yersiniabactin and aerobactin systems in all but one of the ovine strains tested is surprising, since it has been claimed that aerobactin is much more stable than enterobactin and less pH dependent, and is therefore essential for survival of invasive strains within the host [13].…”
Section: Discussionsupporting
confidence: 90%
“…The presence of aerobactin biosynthetic genes in avian septicemic E. coli is in agreement with previous reports which found that most of these strains carry a plasmidencoded aerobactin iron uptake system [7]. However the lack of both yersiniabactin and aerobactin systems in all but one of the ovine strains tested is surprising, since it has been claimed that aerobactin is much more stable than enterobactin and less pH dependent, and is therefore essential for survival of invasive strains within the host [13].…”
Section: Discussionsupporting
confidence: 90%
“…Enterochelin is less effective in vivo, since it interacts with albumin (25). In contrast, aerobactin is effective in vivo and even in an acidic environment such as inflamed tissues, and has therefore been suggested to contribute to virulence (26,39). However, no significant differences were evident in the Lf-binding capacity between aerobactin-producing and non-producing strains.…”
Section: Discussionmentioning
confidence: 99%
“…These results have important implications for the use of cloacin DF13 in the screening of clinical isolates of E. coli or Shigella or Klebsiella species for the presence of aerobactin receptor proteins. The screening of strains for susceptibility to cloacin DF13 has been used on several occasions recently to assess the expression of an aerobactin receptor (17,20,23). Clearly there is a need for caution in interpreting the results of such studies since most wild isolates of the family Enterobacteriaceae synthesize smooth, 0 antigen-carrying LPS which may shield the receptor and prevent binding of the cloacin DF13.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the differences between the susceptibility of S. flexneri and E. coli(pColV) to cloacin action reflected differences in the binding of the bacteriocin to the receptor or differences in other steps in the killing process was not clarified. The possibility that the 0-antigenic chains of lipopolysaccharide (LPS) could interfere with the lethal action of cloacin DF13 on certain smooth strains of E. coli was raised by Lafont et al (17). In the present study, we characterized further the aerobactin-mediated iron uptake system of S. flexneri, paying particular attention to the iron-regulated 76-kDa protein.…”
mentioning
confidence: 86%